2022
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_668_21
|View full text |Cite
|
Sign up to set email alerts
|

Burden of depression and its predictors among prisoners in a central jail of Odisha, India

Abstract: Background Mental illness disproportionately affects the physical, psychological, and social well-being of prisoners worldwide at a far higher rate than the general population. Depression is one of the common mental illnesses. However, in low- and middle-income countries, relatively little research has been undertaken to assess the prevalence and the factors that contribute to depression among prisoners. Aim: This paper aims to assess the burden and predictors of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The present study shows that prevalence of anaemia is higher as compared to study conducted by. 2,3 The present study also revealed that prevalence of depression among study participants higher as compared to study conducted by [4][5][6] however the study conducted by 7,8 shows higher results as compared to present study.…”
Section: Discussionsupporting
confidence: 44%
“…The present study shows that prevalence of anaemia is higher as compared to study conducted by. 2,3 The present study also revealed that prevalence of depression among study participants higher as compared to study conducted by [4][5][6] however the study conducted by 7,8 shows higher results as compared to present study.…”
Section: Discussionsupporting
confidence: 44%
“…In the prison in the Hadoti district in the state of Rajasthan, many people with mental health issues have lower levels of psychiatric treatment available to them, and the standards of treatment are very poor (Kumar and Daria, 2013). A cross-sectional study conducted among male inmates of the central jail in the state of Odisha supports the finding that onefourth of the prisoners were suffering from moderate to severe forms of depression, which was predicted by factors like high educational qualifications, false accusations, and a lack of social support (Tripathy et al, 2022).…”
Section: Prevalence Of Psychological Morbidity Among Prisonersmentioning
confidence: 93%
“…The presence of pili, capsular polysaccharide, DNase, coagulase, fibrinolysin, proteolytic, haemolysin, bacteriocin production, haemagglutination, serum sensitivity, attachment of epithelial cells, hydrophobicity, lipase, antiphagocytic factor (coagulase), biofilm, extracellular enzyme production, presence of surface layer, lysine decarboxy [38]. Accordingly, the existence of these virulent characteristics (Dnase, lecithin, motility, amylase, haemolysin and capsule) in the bacterial isolates of the present study could imply that they are pathogenic and could cause infections or disorders when given the proper infective dose.…”
Section: Virulence Of Isolatesmentioning
confidence: 99%